Efektivitas PjBL dan PBL Pada Penerapan K3LH Bengkel SMKN 3 Toraja Utara: Effectiveness Of PjBL and PBL in K3LH Workshop Learning at SMKN 3 Toraja Utara - Megasari Angki Bunga; Musa B. Palungan; Atus Buku (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
This study aims to analyze the effectiveness of PjBL and PBL in K3LH learning during workshop practice at SMK Negeri 3 Toraja Utara. This research employed a quantitative approach with a quasi-experimental design. The research sample consisted of 80 eleventh-grade students from the Heavy Equipment Engineering and Welding Engineering departments, divided into PjBL and PBL groups, with 40 students in each group. Data were collected through pretest, posttest, questionnaires, observation, and documentation. The data were analyzed descriptively and inferentially using the Shapiro-Wilk test, Wilcoxon Signed-Rank Test, effect size, independent sample t-test, and multiple linear regression. The results showed that both PjBL and PBL significantly improved students’ K3LH knowledge. The PjBL group showed an increase in the mean score from 20.85 to 24.98, with an effect size of 0.766, while the PBL group increased from 24.65 to 27.00, with an effect size of 0.604. In terms of K3LH implementation, there was no significant difference between the PjBL and PBL groups based on observation scores, with a p-value of 0.8047. The regression results indicated that knowledge and attitude had a significant effect on students’ K3LH implementation, while the learning method did not have a significant effect. Therefore, both PjBL and PBL can be used in K3LH learning; however, K3LH implementation in workshop practice is more strongly influenced by students’ knowledge and attitude.